Ramona Quimby, Age 8 : Ramona Quimby Series #6 - Cleary, Beverly, 1916-; Dockray, Tracy (New York : Harper Collins, 1992)
The further adventures of the Quimby family as Ramona enters the third grade.
NewbHB
A
Not
SLJ
Keywords: Family life -- Fiction; Families -- Fiction